Уход Льва Толстого (1910) в оценке русской и польской прессы - Piotrowska, Joanna (Acta Polono-Ruthenica, 2018)
The paper discusses reactions of Russian and Polish (first of all - Warsaw) press to the famous Leo Tolstoy’s escape from Yasnaya Polyana in 1910. A comparison between publications shows that Polish newspapers wrote relatively much and regularly about the event, but interpreted it in a different way than the Russian ones. While the Russian press explained Tolstoy’s escape mostly in the context of his beliefs and views, the Polish one clarified the situation through the personality of the writer, as an act of an extraordinary person or a desperate step of a madman or of a pretender (such interpretation was also presented by the Russian conservative press). This fundamental difference in interpretation can be explained first of all by another status, which Tolstoy had between the Russian and Polish people - for the Poles he was mainly not, as in Russia, a moral authority, but an outstanding writer. Tolstoy’s world-view could also play an important role, especially his religious views, and the significance of Catholicism for the Polish people as one of the most important elements of the national identity.